Analysis and Compensation of Relative Humidity and Ice Formation Effects for Radar-Based SHM Systems Embedded in Wind Turbine Blades - Simon, Jonas; Moll, Jochen; Krozer, Viktor; Kurin, Thomas; Lurz, Fabian; Bagemiel, Oliver; Krause, Stefan (EUROPEAN WORKSHOP ON STRUCTURAL HEALTH MONITORING (EWSHM 2022), VOL 3, 2023)
CRIS-Team WoS Importer:2022-11-11

Analysis of a Physically-Embedded Radar Sensor System - Kurin, Thomas; Issakov, Vadim; Erhardt, Stefan; Weigel, Robert; Lurz, Fabian (2021 18TH EUROPEAN RADAR CONFERENCE (EURAD), 2021)
CRIS-Team WoS Importer:2022-08-26

An Open-Source Speech Codec at 450 bit/s with Pseudo-Wideband Mode - Erhardt, Stefan; Kurin, Thomas; Lurz, Fabian; Weigel, Robert; Kölpin, Alexander (European Microwave Conference 2019, 2019)

A Novel Noninvasive Micro-Doppler-Radar-Based Beehive Monitoring System - Kurin, Thomas; Horlbeck, Marie; Dafner, Marion; Dorn, Christian; Reißland, Torsten; Weigel, Robert; Lurz, Fabian (Asia-Pacific Microwave Conference Proceedings, APMC, 2023)
This paper demonstrates a new noninvasive sensor system to acquire information about a beehives' health using the micro-Doppler of a FMCW radar at 60 GHz. The possibility to track the presence of the queen bee as well as the general hive activity is demonstrated.
CRIS-Team Scopus Importer:2024-12-16
Keywords: beehive; FMCW; Micro-Doppler; sensor node

Antenna Model and Simulation Platform for Angle Estimation with a SISO Radar System - Gabsteiger, Jasmin; Kurin, Thomas; Dorn, Christian; Koelpin, Alexander; Lurz, Fabian (European Microwave Week, 2024)
This paper presents a novel concept for achieving angular estimation and target separation using a bistatic single input single output mmWave radar system operating at 60 GHz. A simulation framework was designed to investigate the antenna configuration required for angle estimation using beam squinting. With this concept, two targets at the same distance and velocity can be separated in angle using power evaluation of range-Doppler plots with constant false alarm rate detection. The simulations were verified with measurements. This proof of concept paves the way to an affordable mmWave single input single output radar system with the capability of angle estimation complementing such systems usually limited to range-Doppler monitoring without angular separatio

A Supercapacitor Powered Radar Sensor Node for Lamination into Wind Energy Rotor Blades - Kurin, Thomas; Erhardt, Stefan; Weigel, Robert; Lurz, Fabian (2021 IEEE Radio & Wireless Week, 2021)
This paper presents a low power sensor node that is embedded into glass fiber composite material of rotor blades during production. The structural condition of the rotor blade is monitored by an integrated FMCW radar. The sensor can achieve a lifetime of 20+ years due to the longevity of a supercapacitor based energy supply. As the available power is low, special consideration must be given to energy saving and system up-time optimization. The concept was proven by embedding the sensor in epoxy resin and consecutively in test sheets produced like rotor blade materia
Keywords: Electronic circuits; Low-power electronics; Sensor node; Supercapacitors; Radar

A Wireless Lightweight System Node for Energy Efficient Beehive Sensing - Kurin, Thomas; Horlbeck, Marie; Maiwald, Timo; Weigel, Robert; Lurz, Fabian (2023 IEEE Topical Conference on Wireless Sensors and Sensor Networks, WiSNeT 2023, 2023)
This paper discusses a novel ultra low power sensor system for monitoring a beehives' health condition, which can be determined by measuring internal temperature and humidity variations. It comprises an autonomous battery powered sensor node which transmits the measured data over a 868 MHz wireless radio link. Expected runtime is greater than 2.1 years.
CRIS-Team Scopus Importer:2023-03-17
Keywords: beehive; ultra low power; WSN

Deep Learning-based Person Detection on a Moving Robot - Gabsteiger, Jasmin; Maiwald, Timo; Kurin, Thomas; Dorn, Christian; Weigel, Robert; Lurz, Fabian (Radio and Wireless Week, 2024)

Design and Evaluation of a Joint Communication and Sensing System Using FMCW-Radar and FSK in V-Band - Faghih-Naini, Samira; Peters, Sebastian; Kurin, Thomas; Reißland, Torsten; Weigel, Robert (20th European Radar Conference (EuRAD 2023), 2023)

Design of a Super Heterodyne Receiver with Double Conversion for Passive Radar with FM Radio - Horlbeck, Marie; Kurin, Thomas; Scheiner, Benedict; Weigel, Robert; Lurz, Fabian (Asia-Pacific Microwave Conference Proceedings, APMC, 2023)
In this paper a frequency selective super heterodyne receiver with double conversion for passive radar with FM radio is presented. Multiple receiver channels allow the processing of eight useful signals. In addition, to minimize signal crosstalk, a low cost shielding cover is made of aluminum plates to avoid expensive milled work.
CRIS-Team Scopus Importer:2024-12-16
Keywords: passive radar; super heterodyne receiver

Direct Sampling Receiver with an Adjustable Bandpass Filter for Use in Passive Radar with FM Radio - Horlbeck, Marie; Fiedelak, Jonathan; Kurin, Thomas; Scheiner, Benedict; Weigel, Robert; Lurz, Fabian (2024 IEEE Radio and Wireless Symposium (RWS), 2024)
This paper presents a direct sampling receiver with an adjustable bandpass filter for passive radar with FM radio. The adjustable bandpass filter allows the advantages of a direct sampling receiver, such as its good linearity properties, to be exploited without the use of additional attenuators at high signal levels, which leads to an increased noise figure, or narrowband filters with a fixed centre frequency, which limits the flexibility in the selection of the useful signal.
CRIS-Team Scopus Importer:2024-03-15
Keywords: adjustable filter; digitally tuneable capacitance; direct sampling receiver; passive radar

Embedded radar networks for damage detection in wind turbine blades: validation in a full-scale fatigue test - Simon, Jonas; Kurin, Thomas; Moll, Jochen; Bagemiel, Oliver; Wedel, Raphael; Krause, Stefan; Lurz, Fabian; Nuber, Andreas; Issakov, Vadim; Krozer, Viktor (Structural Health Monitoring-An International Journal, 2023)
This paper presents the design and experimental realization of a cooperative radar network for structural health monitoring (SHM) of wind turbine blades. For this purpose, 40 FMCW (frequency-modulated continuous wave) radar sensors operating from 58 to 63.5 GHz have been installed in a 31-m-long blade during manufacturing. A subset of 10 sensors is material-embedded in the core material of the blade, and the remaining thirty sensors are placed inside the blade on an inner rotor blade surface. The sensors are distributed over the entire blade based on previous high-frequency electromagnetic simulations. A full-scale fatigue test has been performed under controlled laboratory conditions. In addition, holes have been drilled into the blade by hand to represent a well-defined and relatively small damage. During the experimental campaign, measurements from the complete radar network have been transferred to a base station through a wireless communication link. Finally, it was demonstrated that fatigue as well as artificial damage could be detected accurately using the proposed damage indicator (DI) approach.
CRIS-Team Scopus Importer:2023-04-07
Keywords: damage detection; fatigue testing; radar sensor network; Radar-based SHM; wind turbine blades

Low-Cost, High-Stability Arbitrary Clock Source Using Software GNSS Drift Correction - Dorn, Christian; Kurin, Thomas; Gabsteiger, Jasmin; Lurz, Fabian; Hagelauer, Amelie (4th IEEE MTT-S Latin America Microwave Conference, LAMC 2023 - Proceedings, 2023)
Clock drift is a major challenge for most RF systems in the field. There are many different solutions to obviate or compensate clock drift in these applications, though most are very complex and expensive. In this publication we present an arbitrary clock source, that uses a hybrid phase-locked loop concept to compensate drift of an oven-controlled oscillator by using an integrated clock synthesizer circuit. This allows for a cost effective design, that can use global satellite navigation systems, internal and external temperature sources, an aging model and automatic frequency control information from RF transceivers as an error correction source for the clock drift.
CRIS-Team Scopus Importer:2024-12-16
Keywords: frequency synchronization; GNSS; GPSDO; time synchronization

Optimized Placement for Embedded Radar and Communication Sensors in Wind Turbine Blades - Simon, Jonas; Moll, Jochen; Krozer, Viktor; Kurin, Thomas; Nuber, Andreas; Bagemiel, Oliver; Krause, Stefan; Issakov, Vadim (Structural Health Monitoring 2021: Enabling Next-Generation SHM for Cyber-Physical Systems - Proceedings of the 13th International Workshop on Structural Health Monitoring, IWSHM 2021, 2021)
The present work describes the simulation procedure to determine an optimal sensor placement for RadCom (radar and communication) sensors operating in the frequency band from 57-63 GHz inside a wind turbine blade. Optimal placement means a full penetration and coverage of the blade as well as a communication path from every node to the blade’s root can be achieved. Furthermore, triple coverage is necessary to allow the localization of structural changes in the blade and its surface, such as ice aggretion. The sensors are partly applied to the surface and partly embedded in the core material of the rotor blade. In this way the blade can be monitored during the entire operation for structural health monitoring (SHM) purposes. The simulations take into account the transmission of waves, refraction, dispersion in the material and are based on material data obtained from measurements of rotor blade materials, as well as antenna data. The resulting sensor distribution is the basis for a prototype design of a 30 m long blade with embedded sensors for full-scale SHM testing. Since embedded sensors are not accessible after completion of the manufacturing process, the simulation results are key to the experiments success.
CRIS-Team Scopus Importer:2024-12-16

Radar-based monitoring of glass fiber reinforced composites during fatigue testing - Moll, Jochen; Maetz, Thomas; Maelzer, Moritz; Krozer, Viktor; Mischke, Kevin; Krause, Stefan; Bagemiel, Oliver; Nuber, Andreas; Kremling, Stefan; Kurin, Thomas; Lurz, Fabian; Weigel, Robert; et al. (Structural Control & Health Monitoring, 2021)
This work aims at radar sensors in the frequency band from 57 to 64 GHz that can be embedded in wind turbine blades during manufacturing, enabling non-destructive quality inspection directly after production and structural health monitoring (SHM) during the complete service life of the blade. In this paper, we show the fundamental damage detection capability of this sensor technology during fatigue testing of typical rotor blade materials. Therefore, a frequency modulated continuous wave (FMCW) radar sensor is used for damage diagnostics, and the results are validated by simultaneous camera recordings. Here, we focus on the failure modes delamination, fiber waviness (ondulation), and inter-fiber failure. For each failure mode, three samples have been designed and experimentally investigated during fatigue testing. A damage index has been proposed based on residual, that is, differential, signals exploiting measurements from pristine structural conditions. This study shows that the proposed innovative radar approach is able to detect continuous structural degradation for all failure modes by means of gradual signal changes.
CRIS-Team Scopus Importer:2021-07-02
Keywords: damage detection; fatigue testing; glass fiber reinforced materials; radar-based structural health monitoring; wind turbine blades

Signal Processing for Low-Power and Low-Cost Radar Systems in Bicycle Safety Applications - Dorn, Christian; Kurin, Thomas; Erhardt, Stefan; Lurz, Fabian; Hagelauer, Amelie (2022 IEEE Topical Conference on Wireless Sensors and Sensor Networks, WiSNeT 2022, 2022)
In this publication a miniaturized low-power radar system is introduced that allows detection, tracking and measurement of motorized vehicles passing a bicycle rider. The main focus of this paper is to show a system that is responding with a situation adapted modulation to different measurement requirements while keeping power consumption and BOM cost to a minimum. This is achieved with using an integrated 60 GHz radar and a STM32 ultra-low-power microcontroller for the required signal processing.
CRIS-Team Scopus Importer:2022-04-15
Keywords: dsp; edge computing; FMCW; radar

Towards Embedded Radcom-Sensors in Wind Turbine Blades: Preliminary Numerical and Experimental Studies - Simon, Jonas; Moll, Jochen; Krozer, Viktor; Kurin, Thomas; Lurz, Fabian; Weigel, Robert; Krause, Stefan; Bagemiel, Oliver; Nuber, Andreas; Issakov, Vadim (Progress in Electromagnetics Research Letters, 2020)
This paper presents a numerical study on the application of radar and communication (RadCom) sensor nodes operating in the frequency band from 57-64 GHz. The sensor nodes are embedded in the laminate of wind turbine blades, enable a quality inspection directly after rotor blade manufacturing as well as a structural health monitoring (SHM) throughout the service life of the blade. Given by a lack of dielectric properties for typical rotor blade materials, we have performed experimental studies on material characterization including glass fibre composites, balsa wood, infusion glue, etc. This material database serves as input for wave propagation simulations in a full scale 3D rotor blade model. The analysis also includes a parametric study on path losses as well as an optimal sensor placement strateg

Transceiver Setup for Joint Communication and Sensing Applications in V-Band - Faghih-Naini, Samira; Peters, Sebastian; Kurin, Thomas; Erhardt, Stefan; Reißland, Torsten; Weigel, Robert (IEEE Radio and Wireless Symposium (RWS), 2023)
A new transceiver setup for joint communication and sensing (JCAS) application in V-band with a 3 dB bandwidth of 2.57GHz is presented in this work. With new communication standards like 6G and a rising amount of wireless transmitted data, new transceiver setups for higher carrier frequencies and larger bandwidth need to be developed. The new transceiver setup has differential IQ input ports and a carrier frequency ranging from 57 GHz to 64 GHz. For the proof of radar and communication applications, the reflected IQ signal was detected, and the usability confirmed. This setup can be used for JCAS applications in meter range with high resolution and data rates. <br
Keywords: millimeter wave circuits; millimeter wave communication; millimeter wave radar; transceiver